An overview on the present status and future prospects of pelagic finfish resources of India - Pillai, P P (Indian Journal of Fisheries, 2011)
The results of the studies on stock assessment made on II commercially important pelagic fish groups suchas oil sardine. lesser sardines, whitebaits, mackerel, tunas and billfishes, seerflShes, pomfrets, carangids,ribbonfishes, Bombay duck and Hilsa shad based on the data of 1984-88 are presented. Detailed analysis of theproduction and estimated catchable potential of major pelagic fish groups from the initial stages of mechanizationto recent years and in the traditional fishing areas ofboth the coasts oflndia are indicated. The species whichhave reached the optimal level of exploitation and those which hold potential for further exploitation have beendescribed. The results indicated that the stocks of oil sardine, mackerel, tunas, seerfishes, pomfrets and Bombayduck in the traditional fishing grounds are exploited to or beyond their maximum sustainable yield, whereaslesser sardines, whitebaits and allied species, oceanic tunas frequenting the shelf waters, carangids andribbonfishes have potential for marginal increase. Options open to obtain increase in production to the level ofpotenti8I estimates are briefly discussed, and the necessity of better post-harvest utilization of these finfishespointed out.